Reactive Oxygen Species Regulate the Levels of Dual Oxidase (Duox1-2) in Human Neuroblastoma Cells - Damiano, Simona; Fusco, Roberta; Morano, Annalisa; De Mizio, Mariarosaria; Paternò, Roberto; De Rosa, Antonella; Spinelli, Rosa; Amente, Stefano; Frunzio, Rodolfo; Mondola, Paolo; Miot, Francoise; Laccetti, Paolo; et al. (PLOS ONE, 2012)
Dual Oxidases (DUOX) 1 and 2 are efficiently expressed in thyroid, gut, lung and immune system. The function and the regulation of these enzymes in mammals are still largely unknown. We report here that DUOX 1 and 2 are expressed in human neuroblastoma SK-N-BE cells as well as in a human oligodendrocyte cell line (MO3-13) and in rat brain and they are induced by platelet derived growth factor (PDGF). The levels of DUOX 1 and 2 proteins and mRNAs are induced by reactive oxygen species (ROS) produced by the membrane NADPH oxidase. As to the mechanism, we find that PDGF stimulates membrane NADPH oxidase to produce ROS, which stabilize DUOX1 and 2 mRNAs and increases the levels of the proteins. Silencing of gp91phox (NOX2), or of the other membrane subunit of NADPH oxidase, p22phox, blocks PDGF induction of DUOX1 and 2. These data unravel a novel mechanism of regulation of DUOX enzymes by ROS and identify a circuitry linking NADPH oxidase activity to DUOX1 and 2 levels in neuroblastoma cells.